OpenAIRE compatibility for DSpace repositories - Príncipe, Pedro (2014)
Workshop at Open Repositories 2014, Helsinki, Finland, June 9-13, 2014; Workshops and Tutorials; The OpenAIRE Guidelines for Literature Repositories provide orientation for repository managers to define and implement their local data management.